Farmers’ Willingness to Pay Bio-Activators to Maintain Soil Fertility - Rahayu Relawati; Aniek Iriany; Indah Prihartini; Mona Fairuz Ramli (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
How farmers are willing to pay bio-activators needs to bestudied. The purposes of this study are to analyze theknowledge and use of bio-activators, as well as thewillingness to pay for bio-activators in rice farming. Theresearch was conducted in Malang Regency, with a sampleof 82 farmers from Ngajum and Gondanglegi Districts. Datawere analyzed by descriptive and multiple linear regression.The results showed that the farmers are aware of one tofour brands of bio-activators, and three of the brands areused by the rice farmers. The benefits of using bioactivators that are mostly perceived by rice farmers arefertilizing the soil and plants, thereby increasing theproduction of rice farming. Willingness to pay for bioactivators is based on the prevailing market price, there isno willingness to pay a premium price. Factors that have apositive effect on willingness to pay are land area andbenefits of bio-activators. The wider the agricultural landowned by the farmer and the greater the perceived benefits,the greater the value of willingness to pay will be. Thisinformation can be taken into consideration formanufacturers of bio-activators as a new introductionbefore being released in the market.